Resistance of Coated and Uncoated IR Windows to Seawater Corrosion. - Stachiw ,J D; Bertic,S L (1979)
Germanium and chalcogenide glass specimens were submerged to a 35-foot depth in San Diego Bay for 4 months and the deterioration of their surfaces noted. Some of the specimens were bare, some were protected with a single-layer anti-reflective (AR) IR coating, the remainder were coated with either polyolefine, polyethylene, or polypropylene plastic surcoat. To simulate different operational scenarios to which a submarine-mounted IR window may be subjected, some of the specimens were exposed to natural water circulation, others to water velocities of 6 feet per second. Additionally, some of the submerged specimens were heated by an electric current to simulate de-icing procedures in an arctic environment. Unprotected germanium was found to corrode rapidly while chalcogenide AMTIR-1 glass exhibited excellent corrosion resistance. All plastic surcoats failed by separation from the specimens due to presence of pinholes and water permeability. Anti-reflective coatings deteriorated also, but the transmission of the best single layer AR coating tested (Exotic Materials No. 40104) decreased only five percent, even though presence of pinholes in the coating generated many shallow ( 0.010 inch) corrosion craters in the surfaces of the germanium specimens. Passage of electric current through germanium accelerated the rate of corrosion; one hour of current flow produced more corrosion to the wetted window surface than 8000 hours without electric current. Next phase of testing will cover not only improved single layer, but also durable multilayer AR coatings that promise to extend the life of germanium windows in seawater to 12 months. (Author)